STRATEGI PENGEMBANGAN PRODUK UNGGULAN HASIL INDUSTRI EKONOMI KREATIF DI KOTA PALANGKA RAYA - Wijaya, Novita Chandra (JURNAL SOCIOPOLITICO, 2023)
Novita Chandra Wijaya, 2015. Product Development Strategy Creative Economy Industry Leading Results In the city of Palangkaraya. Thesis Master of Science in Management, Graduate University of Palangkaraya. Under the guidance of the Danes Jaya Negara and Tresia Kristiana. This study aims to: 1). Specify 1 (one) of the most superior type of product from each group of craftsmen, entrepreneurs Material Wood household furniture and household furnishings Entrepreneur Material Aluminum types of industrial products of the creative economy in the city of Palangkaraya based on existing criteria. 2). Develop strategies and policies for the development of 1 (one) of the most superior products from each group creative economy in the city of Palangkaraya namely the craftsmen, entrepreneurs group Material Wood household furniture and household furnishings Employers group Material Aluminium based strengths, weaknesses, opportunities and challenges in its development efforts. This research method through a systematic and structured approach. Systematic approach in which aspects of the research is always based on the aspect of Internal and External Aspects, both the potential and problems. While structured approach, namely: step strategy formulation always begins with identifying and assessing aspects of Internal and External Aspects, which was then followed by combining both aspects. Based on the analysis of Expert Choice AHP program version 11.0 for a data value interest Saaty scale as calculation (attached) and SWOT analysis obtained results of the analysis can be concluded that: 1). The most superior product yield creative economy industry for this type of business in the city of Palangkaraya Crafts is Anyaman Rotan, industry for this type of business processing industry Appliances Wood materials is the type Lemari Kayu, and industry for this type of industry efforts Appliances Processing of Aluminium materials is the type Etalase. 2). The strategy should the government do Palangkaraya to develop Anyaman Rotan Crafts, Household Furniture Material Wood Wardrobe in particular types of products and Appliances Material Aluminum particular types of products Showcase by building industry materials processing semi-finished and finished materials of rattan, wood and aluminum, open up investment opportunities widest, capital, possible market, improve service quality products, provide centers of the sale of products, improve the promotion, improve price stability, improve the quality of human resources, improving quality design products, develop innovative types of products, develop marketing research activities and processing, applying environmentally friendly technologies. 3). Measures taken in the form of trade policies rattan, wood and aluminum in essence swinging from one side to the opposite side with a slight variation. Swing to one side benefit manufacturers of rattan, wood and aluminum raw and consumer detriment processing industry as rattan, wood and aluminum raw, while others harm producers swing rattan, wood and aluminum raw and benefit consumers.